IMPLEMENTASI PJBL PADA MATERI TEKS PROSEDUR KELAS 7 SMP NEGERI 37 SEMARANG - Cahyaningdyah Arumingtyas; Sri Mahmudah; Ika Septiyana (STKIP Subang, 2024)
ABSTRACT This study aims to examine the effectiveness of the implementation of the Project-Based Learning (PjBL) learning model in improving the writing skills of procedural texts in grade VII students of SMP Negeri 37 Semarang. Writing skills, which require organizing ideas effectively, are often a challenge for students. Using a qualitative descriptive design, data were collected through observation, interviews, and documentation. The research procedure involved a diagnostic assessment stage to determine students' learning styles, dividing groups based on learning interests, creating procedural texts in audio-visual, visual, and infographic formats, and presenting group project results. The results showed that the implementation of PjBL was effective in improving students' writing skills. Students were able to understand procedural texts more deeply and express their understanding through various creative media. In addition, this learning process encouraged the development of 21st-century skills, such as critical thinking, collaboration, and creativity. However, constraints such as time constraints and low literacy in some students were challenges in this study. The proposed solutions include more mature time planning and intensive guidance from teachers for students with low literacy. In conclusion, the PjBL model has a positive impact on learning procedural texts and supports the development of students' overall competencies. This study recommends better preparation of time allocation and provision of supporting resources for successful implementation in the future. These findings provide important contributions in the development of innovative and relevant learning methods to improve the quality of Indonesian language learning in secondary schools.